The Appetite Suppressant D-norpseudoephedrine (Cathine) Acts via D1/D2-Like Dopamine Receptors in the Nucleus Accumbens Shell - Kalyanasundar, B.; Perez, Claudia I.; Arroyo, Benjamin; Moreno, Mario Gil; Gutierrez, Ranier (Frontiers in Neuroscience, 2020)
D-norpseudoephedrine (NPE), also known as cathine, it is found naturally in the shrub Catha edulis “Khat.” NPE has been widely used as an appetite suppressant for the treatment of obesity. Although it is known that NPE acts on α1-adrenergic receptors, there is little information about the role of dopamine receptors on NPE's induced anorectic effects. Equally untouched is the question of how NPE modulates neuronal activity in the nucleus accumbens shell (NAcSh), a brain reward center, and a pharmacological target for many appetite suppressants. To do this, in rats, we characterized the pharmacological effects induced by NPE on weight loss, food intake, and locomotion. We also determined the involvement of dopamine D1 and D2-like receptors using systemic and intraNAcSh antagonists, and finally, we recorded single-unit activity in the NAcSh in freely moving rats. We found that NPE decreased 24 h food intake and leads to weight loss, and as side effects increased locomotor activity and wakefulness. Also, both intraperitoneal and intraNAcSh administration of D1- and D2 dopamine antagonists partially reversed NPE’s induced weight loss and food intake suppression. Furthermore, the D1 antagonist, SCH-23390, eliminated NPE-induced locomotion, whereas the D2 antagonist, raclopride, only delayed its onset. We also found that NPE evoked a net activation imbalance in NAcSh’s that propelled the population activity trajectories into a dynamical pharmacological brain state, that correlated with the onset of NPE-induced wakefulness. Together, our data demonstrate that NPE modulates NAcSh spiking activity and that both dopamine D1 and D2 receptors are necessary for NPE’s-induced food intake suppression and weight loss.